2000
DOI: 10.1046/j.1365-2109.2000.00501.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth and survival of the Calafia mother-of-pearl oyster Pinctada mazatlanica (Hanley 1856) under different sequences of nursery culture-late culture at Bahía de La Paz, Baja California Sur, México

Abstract: The Calafia mother‐of‐pearl oyster, Pinctada mazatlanica (Hanley), and the Rainbow nacre shell, Pteria sterna (Gould), represent an important resource for México because of their potential in pearl production. The present work deals with the effect of different sequences of nursery culture‐late culture on growth and survival of P. mazatlanica, from September 1993 to October 1994. The collected spat presented two main size groups: small (mean shell height of 7 mm), and large (13 mm). They were arranged into fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…The small seeds of pearl oysters are more vulnerable, as shown by Monteforte and Morales-Mulia (2000), whom also recommend a careful handling, with a frequency of 2 months, in order to avoid damage to the byssus. They also pointed out the necessity to further study the stock density and cleaning effects on P. mazatlantica.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The small seeds of pearl oysters are more vulnerable, as shown by Monteforte and Morales-Mulia (2000), whom also recommend a careful handling, with a frequency of 2 months, in order to avoid damage to the byssus. They also pointed out the necessity to further study the stock density and cleaning effects on P. mazatlantica.…”
Section: Discussionmentioning
confidence: 99%
“…They also pointed out the necessity to further study the stock density and cleaning effects on P. mazatlantica. However, for Pinctada mazatlantica, as well as for Pteria sterna, preliminary studies indicated that the collectors should be recovered not later than 3 months after immersion, otherwise high seed mortality can occur as a result of predation and competition among associated species (Monteforte and Garcia-Gasca, 1994;Monteforte and Wright, 1994;Monteforte et al, 1995;Wright, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Culture artifacts and pearl oysters were surveyed monthly (cleaning, counting, measuring, repartition), and salinity (ppm) and water temperature (°C) were recorded. At the end of nursery culture, half of the surviving individuals of each D group were transferred into sandwich nets (S) which were vertically suspended at a depth of 10-11 m. The other half were transferred to rail cages (C) which were placed horizontally over iron rod structures on the sea bottom at a depth of 12 m. Details of manufacture and management can be seen in Monteforte and Morales (2000). Individuals were arranged in rows along the shelves of these artifacts.…”
Section: Experimental Designmentioning
confidence: 99%
“…We used shell volume (cm 3 ) and mortality incidence (%) as indicators for treatment evaluation. Shell volume allowed more consistent interpretation of growth trends in P. mazatlanica (Saucedo et al 1998;Monteforte and Morales 2000).…”
Section: Introductionmentioning
confidence: 96%